Countering the Cycle-The Effectiveness of Fiscal Policy in Korea - Eskesen, Leif (IMF Working Papers; Working Paper ;, 2009)
The Korean authorities having taken decisive and proactive fiscal measures to help stem the fallout from the current global economic and financial crisis, with the size of the fiscal stimulus well-above the average response of other G20 economies. In this context, a key question is how effective fiscal policy is as a stabilization tool, especially considering the high openness of Korea's economy. Results based on a macroeconomic model calibrated for Korea provide a strong case for using counter-cyclical fiscal policy, especially if measures appropriately focus on spending with a direct demand impact such as investment and targeted transfers. It also demonstrates the importance a complementary monetary response and the benefits to an open economy such as Korea's of global coordination of fiscal stimulus.